Immune regulatory gene polymorphisms, frequent cannabis use, and psychosis: implications to Treg hypofunction. (1st June 2022) - Corsi-Zuelli, F.; Loureiro, C.; Shuhama, R.; Quattrone, D.; Deakin, B.; Menezes, P.; Lacchini, R.; Coeli-Lacchini, F.; Louzada-Junior, P.; Del-Ben, C.
Abstract : Introduction: We have previously shown that the association between frequent cannabis use and psychosis is more likely in subgroups with low-grade inflammation than subgroups without (PMID: 33736715). The role of immune-related polymorphisms remains unknown. Objectives: To explore whether polymorphisms affecting the function of key immune regulatory proteins moderate the association between cannabis and psychosis, namely: ENTPD1 and NT5E, involved in the synthesis of CD39, CD73, respectively, and anti-inflammatory adenosine; CTLA4 and FOXP1, essential for Treg functional capacity. Methods: We genotyped blood samples from 283 community-based controls and 140 recent-onset psychosis patients in Brazil (EU-GEI consortium, Ribeirão Preto/SP) for twelve polymorphisms ( ENTPD1 : rs3814159, rs3176891, rs10748643; NT5E: rs9444348, rs2295890; CTLA4 : rs3087243, rs231775, rs5742909, rs4553808; FOXP1 : rs6803008, rs6786408, rs830599; Illumina Human Core Exome-24). Cannabis frequency (daily, less than daily, never) was assessed by self-report (Cannabis Experience Questionnaire). Binary logistic regression models (OR, 95%CI) included case status as the outcome, genotype (dominant model), cannabis frequency, and an interaction term between the two as exposure, adjusting for confounders (age, sex, ethnicity, tobacco smoking). Results: We found significant interactions between cannabis use and polymorphisms for ENTPD1 (rs3814159), NT5E (rs9444348), and FOXP1 (rs6786408). Less than daily or daily use were, in a dose-response fashion, only associated with psychosis in those with the variant and heterozygous genotypes; less than daily: ENTPD1 AG/GG (3.34, 1.71-6.50); NT5E AG/AA (3.71, 1.87-7.33); FOXP1 AC/CC (2.98, 1.54-5.77); daily: ENTPD1 AG/GG (16.81;5.89-47.96); NT5E AG/AA (21.20, 6.81-66.01); FOXP1 AC/CC (13.75, 5.22-36.21). Conclusions: Variation in genes that affect Treg function appears to modify the effect of cannabis consumption on psychosis in keeping with Treg hypofunction hypothesis (PMID:33713699). Disclosure: No significant relationships.